2015
DOI: 10.1007/s00145-015-9214-4
|View full text |Cite
|
Sign up to set email alerts
|

A Full Proof of the BGW Protocol for Perfectly Secure Multiparty Computation

Abstract: In the setting of secure multiparty computation, a set of n parties with private inputs wish to jointly compute some functionality of their inputs. One of the most fundamental results of information-theoretically secure computation was presented by Ben-Or, Goldwasser and Wigderson (BGW) in 1988. They demonstrated that any n-party functionality can be computed with perfect security, in the private channels model. When the adversary is semi-honest this holds as long as t < n/2 parties are corrupted, and when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 29 publications
0
72
0
Order By: Relevance
“…Moreover, the protocol can be computed with perfect security on the information theoretic model against passive and active adversaries under Canetti's hybrid model [13] by using available MPC protocols such as BGW [7]. We refer the reader to [21] for a complete set of proofs of security and composability for BGW. Indeed, results in BGW [7] and CDD [8] showed that any function can be computed using MPC with the aforementioned security levels by providing secure addition and multiplication under an arithmetic circuit paradigm.…”
Section: Privacy-preserving Protocol For Electricity Tradingmentioning
confidence: 99%
“…Moreover, the protocol can be computed with perfect security on the information theoretic model against passive and active adversaries under Canetti's hybrid model [13] by using available MPC protocols such as BGW [7]. We refer the reader to [21] for a complete set of proofs of security and composability for BGW. Indeed, results in BGW [7] and CDD [8] showed that any function can be computed using MPC with the aforementioned security levels by providing secure addition and multiplication under an arithmetic circuit paradigm.…”
Section: Privacy-preserving Protocol For Electricity Tradingmentioning
confidence: 99%
“…To avoid confusion related to security of the BGW protocol, we want to clarify the relation between our result and the recent security proof for this protocol, given by Lindell and Asharov [2]. They prove static security and then notice that BGW satisfies the MR definition, which by the result from [7] implies adaptive security (in the MR definition).…”
Section: Introductionmentioning
confidence: 75%
“…The analysis follows the standard BGW analysis (detailed in [AL11]). Very roughly, to show correctness, note that by the homomorphic properties of the Reed-Solomon code the correct polynomial E is such that E(0) = C(x 1 , .…”
Section: Output E(0)mentioning
confidence: 99%